Outcome of paediatric lobectomy by thoracotomy — a single centre, six-year experience - Hamza Sohail; Abdul Rehman (Journal of the Pakistan Medical Association, 2022)
Abstract This short report highlights the patient outcome of lung resections for congenital and acquired lung lesions in children who presented to the Liaquat National Hospital, Karachi, from January 2013 to April 2019. Common indications were congenital pulmonary airway malformation (CPAM), congenital lobar emphysema (CLE), and bronchiectasis. Two patients died whereas, 21 were discharged home. Lung resection can be performed safely in children. Early diagnosis and surgery may improve the outcome. Keywords: Lung Diseases, Pulmonary Emphysema, Bronchiectasis, Lobectomy.